The Politics of Silence : Myanmar NGOs' Ethnic, Religious and Political Agenda - Loïs Desaine (Institut de recherche sur l'Asie du Sud-Est contemporaine, 2011)
The political regime in Myanmar used to be a seemingly monopolistic structure where power was exclusively in the Army's hands. A marginal external influence was exercised by businessmen with close ties to the regime while the country is also exposed to the influence of powerful regional states. Since the General Elections in November 2010, the establishment of the Republic of the Union of Myanmar with a parliamentary democracy (which remains under some control of the Army, but with notable civilian representation) is the most noticeable change in Myanmar politics for decades as it may shift the state away from the Army monopoly, although concrete changes remain to be demonstrated.